Safety and efficacy of APSA PHYTAFEED® 20, 000 GR/L (6‐phytase) as a feed additive for turkeys for fattening, turkeys reared for breeding and minor poultry species. (7th November 2019) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the EFSA Panel on Additives and products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety and efficacy of APSA PHYTAFEED ® 20, 000 GR/L (6‐phytase) as a feed additive turkeys for fattening, turkeys reared for breeding and minor poultry species. The additive is a preparation of 6‐phytase produced by a genetically modified strain of Komagataella phaffii and has been previously assessed by the FEEDAP Panel in the context of an application for its use in feed for chickens for fattening. The Panel concluded in that opinion that the production strain is safe, and that the use of the additive as a feed additive would raise no safety concerns for the consumers and the environment. The additive was also considered not to be irritant to skin or eyes or a dermal sensitiser but that should be considered as a respiratory sensitiser. The Panel considered that the new use in turkeys would not modify the previously drawn conclusions with respect to the consumers, users and the environment. A tolerance trial and a subchronic oral toxicity study were made available to support the safety for the new target species. From the results obtained, the FEEDAP Panel concluded that APSA PHYTAFEED ® GR/L is safe for turkeys for fattening at the recommended level of 250 U/kg feed with a wide margin of safety. This conclusion was extended to turkeys reared for breeding. The applicant submitted three efficacy trials to support the efficacy of the additive. In these trials, the utilisation of phosphorus and bone ash/phosphorus content were measured. From the results obtained, the FEEDAP Panel concluded that APSA PHYTAFEED ® GR/L is efficacious for turkeys for fattening, turkeys reared for breeding and minor poultry at the level of 250 U/kg feed.